2014
DOI: 10.14814/phy2.12029
|View full text |Cite
|
Sign up to set email alerts
|

Galacto-oligosaccharides attenuate renal injury with microbiota modification

Abstract: AbstractsTubulointerstitial injury is central to the progression of end‐stage renal disease. Recent studies have revealed that one of the most investigated uremic toxins, indoxyl sulfate (IS), caused tubulointerstitial injury through oxidative stress and endoplasmic reticulum (ER) stress. Because indole, the precursor of IS, is synthesized from dietary tryptophan by the gut microbiota, we hypothesized that the intervention targeting the gut microbiota in kidney disease with galacto‐oligosaccharides (GOS) would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Studies report that prebiotic and/or probiotic treatments results in decreases in uremic toxins such as indoxyl sulfate and p-cresol in humans and animals by improving the gut environment [9, 14]. Additionally, it is reported that prebiotic and/or probiotic treatments ameliorate kidney function in humans and animals by improving the gut environment [24, 25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies report that prebiotic and/or probiotic treatments results in decreases in uremic toxins such as indoxyl sulfate and p-cresol in humans and animals by improving the gut environment [9, 14]. Additionally, it is reported that prebiotic and/or probiotic treatments ameliorate kidney function in humans and animals by improving the gut environment [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…The SCFA produced by bacteria are the major source of energy for colonocytes [27]. Furuse et al [14] reported that the proportion of Bifidobacteriaceae was significantly increased and Ruminococcaceae was decreased in Nx GOS (administration of galacto-oligosaccharides) rats compared with Nx CON rats. Our data were similar to their results in that Bifidobacterium was significantly increased in Nx GFOB rats compared with Nx CON rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 5/6 nephrectomized rats, 2 weeks administration of galacto-oligosaccharides can modify the gut microbiota by increasing 3 bacterial families and decreasing 5 bacterial families, including Clostridiaceae. 90 This finding is associated with a reduction in serum IS levels, cecal indole, endoplasmic reticulum stress and apoptosis, and an improvement of renal injury. 90 A non-randomized phase I/II study of hemodialysis patients demonstrated that administration of prebiotic oligofructose-enriched inulin for 4 weeks significantly reduced serum levels of pCS, but not IS.…”
Section: Renal Endpoints In Preclinical Studiesmentioning
confidence: 94%
“…90 This finding is associated with a reduction in serum IS levels, cecal indole, endoplasmic reticulum stress and apoptosis, and an improvement of renal injury. 90 A non-randomized phase I/II study of hemodialysis patients demonstrated that administration of prebiotic oligofructose-enriched inulin for 4 weeks significantly reduced serum levels of pCS, but not IS. 91 Synbiotics "Synbiotic" treatment uses a combination of probiotics and prebiotics.…”
Section: Renal Endpoints In Preclinical Studiesmentioning
confidence: 94%